Non‐Maxwellianity of Electron Distributions Near Earth's Magnetopause. Issue 10 (11th October 2021) - Graham, D. B.; Khotyaintsev, Yu V.; André, M.; Vaivads, A.; Chasapis, A.; Matthaeus, W. H.; Retinò, A.; Valentini, F.; Gershman, D. J.
Abstract: Plasmas in Earth's outer magnetosphere, magnetosheath, and solar wind are essentially collisionless. This means particle distributions are not typically in thermodynamic equilibrium and deviate significantly from Maxwellian distributions. The deviations of these distributions can be further enhanced by plasma processes, such as shocks, turbulence, and magnetic reconnection. Such distributions can be unstable to a wide variety of kinetic plasma instabilities, which in turn modify the electron distributions. In this paper, the deviation of the observed electron distributions from a bi‐Maxwellian distribution function is calculated and quantified using data from the Magnetospheric Multiscale spacecraft. A statistical study from tens of millions of electron distributions shows that the primary source of the observed non‐Maxwellianity is electron distributions consisting of distinct hot and cold components in Earth's low‐density magnetosphere. This results in large non‐Maxwellianities at low densities. However, after performing a statistical study we find regions where large non‐Maxwellianities are observed for a given density. Highly non‐Maxwellian distributions are routinely found at Earth's bowshock, in Earth's outer magnetosphere and in the electron diffusion regions of magnetic reconnection. Enhanced non‐Maxwellianities are observed in the turbulent magnetosheath, but are intermittent and are typically not correlated with local processes. The causes of enhanced non‐Maxwellianities are investigated. Key Points: Electron non‐Maxwellianity is computed for 6 months of data (85 million electron distributions) Electron non‐Maxwellianity is typically large in the magnetosphere due to hot and cold electron populations Enhanced non‐Maxwellianity is found in reconnection regions, the bowshock, and magnetosheath turbulence